Inсretin-based therapy in patients with type 2 diabetes and chronic kidney disease - Minara Shamkhalovna Shamkhalova; Marina Vladimirovna Shestakova (Сахарный диабет)
The program of renoprotection in patients with diabetes mellitus (DM) is based on a conceptual model of development and progressionof diabetic kidney disease, which is the result of combined impact of genetically modulated metabolic and hemodynamic factors. Compensationof carbohydrate metabolism, which is crucial at the clinical debut of nephropathy, becomes problematic at the late stages ofchronic kidney disease (CKD). ADA (American Diabetes Association) and EASD (European Association for the Study of Diabetes)recommendations formalized in a consensus on the treatment of patients with type 2 diabetes (T2D) should only be extrapolated topatients with CKD with great prudence. Incretin-based drugs gain reputation as promising and perspective therapy for metabolic controlin patients with type 2 DM and CKD. There is an obvious need for large-scale, long-term studies involving patients with various severityof renal disease and related complications to assess the potential of this new diabetes therapy trend.